1990
DOI: 10.1099/00222615-31-2-85
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of specificity and biological activity of polyclonal and monoclonal antibodies raised against Salmonella minnesota R595 lipopolysaccharide

Abstract: Summary. Murine monoclonal antibodies (MAbs) and immune rabbit serum were raised against the rough mutant of Salmonella minnesota strain R595. These antibodies were tested for their ability to inhibit LPS-induced B-cell mitogenicity and neutralise LPS toxicity in chick embryos. Immune rabbit serum inhibited both mitogenicity and LPS lethality. None of the MAbs or a cocktail of antibodies were able to neutralise LPS lethality in chick embryos. However, they were able to inhibit mitogenicity by varying degrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…We find that the Sm5G also inhibited murine splenocyte proliferation induced by R595 lipid A (20). Furthermore, Metha et al (26) have reported that rabbit anti-R595 LPS antiserum inhibited both mitogenicity (murine splenocytes) and lethal toxicity (chick embryo) of the Re LPS, while MAbs inhibited the mitogenesis but were not able to neutralize the lethality.…”
Section: Discussionmentioning
confidence: 99%
“…We find that the Sm5G also inhibited murine splenocyte proliferation induced by R595 lipid A (20). Furthermore, Metha et al (26) have reported that rabbit anti-R595 LPS antiserum inhibited both mitogenicity (murine splenocytes) and lethal toxicity (chick embryo) of the Re LPS, while MAbs inhibited the mitogenesis but were not able to neutralize the lethality.…”
Section: Discussionmentioning
confidence: 99%